2022
DOI: 10.3389/fragi.2021.819903
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of Lipid Metabolic Changes in Drosophila Ovary During Aging Using DO-SRS Microscopy

Abstract: Emerging studies have shown that lipids and proteins play versatile roles in various aspects of aging. High-resolution in situ optical imaging provides a powerful approach to study the metabolic dynamics of lipids and proteins during aging. Here, we integrated D2O probing and stimulated Raman scattering (DO-SRS) microscopy to directly visualize metabolic changes in aging Drosophila ovary. The subcellular spatial distribution of de novo protein synthesis and lipogenesis in ovary was quantitatively imaged and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
3
10
0
Order By: Relevance
“…Both groups showed a positive correlation between LD size and metabolic activity, suggesting that larger LDs have higher metabolic activity. This result is consistent with our studies on Drosophila fatbody metabolic activity (45-47). Importantly, quantitative analyses of CD/CH 2 ratio showed that the average lipid turnover rate in the high glucose group was about 10 times higher than that in the control group, suggesting more newly synthesized lipids were accumulated in flies on high glucose diet (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Both groups showed a positive correlation between LD size and metabolic activity, suggesting that larger LDs have higher metabolic activity. This result is consistent with our studies on Drosophila fatbody metabolic activity (45-47). Importantly, quantitative analyses of CD/CH 2 ratio showed that the average lipid turnover rate in the high glucose group was about 10 times higher than that in the control group, suggesting more newly synthesized lipids were accumulated in flies on high glucose diet (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Both groups showed a positive correlation between LD size and metabolic activity, suggesting that larger LDs have higher metabolic activity. This result is consistent with our studies on Drosophila fatbody metabolic activity (45)(46)(47). Importantly, quantitative analyses of CD/CH 2 ratio showed that the average lipid turnover rate in the high glucose group was about 10 times higher than that in the control group, suggesting more newly synthesized lipids were accumulated in ies on high glucose diet (see Fig.…”
Section: Resultssupporting
confidence: 92%
“…We demonstrate that SRS imaging is capable of detecting cell heterogeneity within live tissue and of providing detailed information about the distribution of d 8 -Met at subcellular resolution. These findings add to the growing evidence showing that SRS imaging of small deuterated biomolecules is a highly versatile and sensitive method for long-term analysis of metabolism, with the potential to track many aspects of metabolism from uptake and distribution to downstream molecular fate ( Wei et al, 2013 ; Wei et al, 2015 ; Wei et al, 2016 ; Shi et al, 2018 ; Li et al, 2021 ; Li et al, 2022a ; Li et al, 2022b ; Fung et al, 2022 ). The high sensitivity and quantification capabilities of SRS imaging make it a useful tool for metabolic profiling with subcellular spatial resolution, and this will be useful for studying metabolism and cellular heterogeneity in a range of biological processes, including protein metabolism in development and diseases such as cancer.…”
Section: Discussionmentioning
confidence: 58%
“…It has been used to label abundant amino acids such as leucine ( Wei et al, 2013 ; Wei et al, 2015 ), as well as multiple amino acids ( Wei et al, 2013 ; Wei et al, 2015 ; Wei et al, 2016 ). In recent work, deuterated water and the model organism Drosophila have further demonstrated the non-invasive nature of deuterium for systemic labelling in vivo and long-term imaging, highlighting its potential as a universal metabolic probe ( Shi et al, 2018 ; Li et al, 2021 ; Li et al, 2022a ; Li et al, 2022b ; Fung et al, 2022 ). However, deuterium’s weaker vibrational resonance can limit the detectable signal, making it less suitable for labeling less abundant single species of biomolecules such as methionine (Met).…”
Section: Introductionmentioning
confidence: 99%